2021
DOI: 10.5194/tc-2021-142
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hyper-accumulation of legacy fallout radionuclides in cryoconite on Isfallsglaciären (Arctic Sweden) and their downstream distribution

Abstract: Abstract. The release of legacy fallout radionuclides (FRNs) in response to glacier retreat is a process that has received relatively little attention to date, yet may have important consequences as a source of secondary contamination as glaciers melt and down-waste in response to a warming climate. The prevalence of FRNs in glacier-fed catchments is poorly understood in comparison to other contaminants, yet there is now emerging evidence from multiple regions of the global cryosphere for substantially augment… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Previous research on cryoconite has often focused on microorganism ecosystems and the ability of cryoconite to accumulate nutrients (Poniecka et al, 2020; Poniecka and Bagshaw, 2021). However, recent research has shown that cryoconite can also act as a sink for pollutants including BC, FRNs and PTEs (Clason et al, 2021; Cong et al, 2018; Fortner and Lyons, 2018; Li et al, 2017; Łokas et al, 2018). Larger pockets of cryoconite called ‘cryoconite holes’ vary in size, but typically have dimensions of 10–100cm 3 (MacDonell and Fitzsimons, 2008, 2012).…”
Section: Contaminant Accumulation and Concentration Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research on cryoconite has often focused on microorganism ecosystems and the ability of cryoconite to accumulate nutrients (Poniecka et al, 2020; Poniecka and Bagshaw, 2021). However, recent research has shown that cryoconite can also act as a sink for pollutants including BC, FRNs and PTEs (Clason et al, 2021; Cong et al, 2018; Fortner and Lyons, 2018; Li et al, 2017; Łokas et al, 2018). Larger pockets of cryoconite called ‘cryoconite holes’ vary in size, but typically have dimensions of 10–100cm 3 (MacDonell and Fitzsimons, 2008, 2012).…”
Section: Contaminant Accumulation and Concentration Mechanismsmentioning
confidence: 99%
“…There is evidence that even low to moderate doses of FRNs within drinking water can increase cancer risk and genetic malformations (WHO, 2008). FRNs have been found in most regions of the global cryosphere, but research has predominantly focused on activity in the northern hemisphere due to the location of many FRN sources, including areas such as the European Alps, Canada, Svalbard, Scandinavia and the Caucasus (Baccolo et al, 2020; Clason et al, 2021; Łokas et al, 2016, 2018, 2021; Owens et al, 2019). FRNs found in high concentrations include 137 Cs, 241 Am and 210 Pb, with some of the highest concentrations found in cryoconite, an organic rich glacial sediment (Baccolo et al, 2020; Łokas et al, 2019).…”
Section: Contaminants In Glaciated Environmentsmentioning
confidence: 99%
See 1 more Smart Citation